Effects of high and low 17β-estradiol doses on focal cerebral ischemia: negative results - Strom, Jakob O. (Sci Rep, 2013)
The reasons why some animal studies indicate that estrogens increase focal cerebral ischemic damage while others show estrogen-induced neuroprotection has hitherto not been fully elucidated. Recent evidence indicates that discrepancies in hormone administration paradigms, resulting in highly different serum hormone concentrations, may account for the dichotomy. The current study aimed to test this hypothesis. Sixty ovariectomized female rats were randomized into three groups differing in 17β-estradiol regimens, and transient focal cerebral ischemia was subsequently induced. All animals were subjected to a small functional testing battery, and three days after MCAo they were sacrificed for infarct size assessment. Infarct sizes did not differ between groups, however clear discrepancies were seen in body weight and feeding behavior. In comparison to sham-operated animals, ovariectomized rats rapidly increased in body weight, whereas the opposite was seen in rats receiving 17beta-estradiol. The weight gain in the ovariectomized rats was paralleled by an increased food intake.